Evaluation of the pH, calcium release and antibacterial activity of MTA Fillapex - Kuga, Milton Carlos [UNESP]; Faria, Gisele [UNESP]; Weckwerth, Paulo Henrique; Duarte, Marco Antonio Hungaro; Campos, Edson Alves De [UNESP]; Só, Marcus Vinicius Reis; Viola, Kennia Scapin [UNESP] (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
OBJECTIVE: This study evaluated, in several analysis periods, pH and calcium release and antibacterial activity provided by MTA Fillapex sealer compared to Sealapex and AH Plus sealers. MATERIAL AND METHOD: Polyethylene tubes were filled with a sealer and immersed in distilled water. After 24 hours, 14 and 28 days, pH and calcium release by endodontic sealers were evaluated directly in water which the tubes were stored. Sealers antibacterial activity was evaluated against Enterococcus faecalis and Staphylococcus aureus by means of agar diffusion test. All data were submitted to ANOVA and Tukey tests (α=0.05). RESULT: In all periods evaluated, Sealapex had the highest pH value (p<0.05) in comparison to other sealers and MTA Fillapex provided higher pH values than AH Plus (p<0.05). In 14-days period, MTA Fillapex had greater calcium release value than Sealapex (p<0.05). In 28-days period, Sealapex provided higher calcium release than MTA Fillapex (p<0.05). In all periods, AH Plus provided lower calcium release than other sealers (p<0.05). In relation to E. faecalis, there were no differences among the sealers, in relation to antibacterial activity (p>0.05). In relation to S. aureus, Sealapex presented better antibacterial effectiveness than the MTA Fillapex and AH Plus (p<0.05), which were similar each other (p>0.05). CONCLUSION: In final evaluation period, pH values and calcium release provided by MTA Fillapex were lower than provided by Sealapex and higher than provided by AH Plus. The MTA Fillapex antimicrobial action was similar to other endodontic sealers.

OBJETIVO: O estudo avaliou, em diversos períodos de análise, o pH e liberação de cálcio e a atividade antibacteriana proporcionada pelo MTA Fillapex, em relação ao Sealapex e AH Plus. MATERIAL E MÉTODO: Tubos de polietilenos foram preenchidos com um dos cimentos e imersos em água destilada. Após de 24 horas, 14 e 28 dias, o valor do pH e o cálcio liberado pelos cimentos foram avaliados diretamente na água destilada em que os espécimes permaneceram imersos. A atividade antibacteriana dos cimentos foi avaliada em culturas de Enterococcus faecalis ou Staphylococcus aureus, por meio do teste de difusão em ágar. Os dados obtidos foram submetidos aos testes de ANOVA e Tukey (α=0.05). RESULTADO: Em todos os períodos analizados, o Sealapex proporcionou os maiores valores de pH (p<0,05) em relação aos demais cimentos e o MTA Fillapex proporcionou maiores valores que o dos AH Plus (p<0,05). Em 14 dias, o MTA Fillapex promoveu maior liberação de cálcio que o proporcionado pelo Sealapex (p<0,05). Em 28 dias, o Sealapex proporcionou maior liberação de cálcio que o MTA Fillapex (p<0,05). Em todos os períodos, o AH Plus apresentou a menor liberação de cálcio em relação aos outros cimentos (p<0,05). Em relação ao E. faecalis, não foram observadas diferenças (p>0,05) entre as zonas de inibição de crescimento bacteriano produzidas pelos diveros cimentos. Em relação ao S. aureus, o Sealapex apresentou maior atividade antibacteriana que o MTA Fillapex e o AH Plus (p<0,05), que por sua vez foram semelhantes entre si (p>0,05). CONCLUSÃO: Após o período final de avaliação, o pH e a liberação de cálcio proporcionado pelo MTA Fillapex foram menores que os do Sealapex e maiores que os do AH Plus. A atividade antimicrobiana do MTA Fillapex não diferiu dos demais cimentos endodônticos.
Avaliação do pH, liberação de cálcio e atividade antibacteriana do MTA Fillapex
Keywords: Calcium; endodontics; Enterococcus faecalis; Staphylococcus aureus; Cálcio; endodontia; Enterococcus faecalis; Staphylococcus aureus